Pengaruh Situation Awareness terhadap Kinerja Petugas Airside di Bandar Udara - Fauziah, Syifa; Rubi, Yosefina Delvina Marleny (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Situation Awareness (SA) is a person's perception or response to be able to understand conditions or circumstances in the surrounding environment. This research aims to find out whether there is an influence of Situation Awareness on the performance of Airside officers and to find out if there is an influence, how much influence Situation Awareness has on the performance of Airside officers at the airport. This research uses a quantitative approach with the variables Situation Awareness (X) and Airside Officer Performance (Y). The population of PT Airside officers. There are 50 people at El Tari Kupang Airport's Angkasa Gate, including 15 AMC officers and 35 Ground Handling officers. Then samples were taken from the total population as a whole and analyzed using Simple Linear Regression using SPSS. The research results show that based on the test results obtained, it can be seen that Situation Awareness (X) influences the performance of Airside Officers (Y) at El Tari Kupang International Airport with the test results obtained with a calculated T value of 15.645 and a significant value of 0.01< 0.05. The result of the coefficient of determination R2 is 0.836 so it can be concluded that Situation Awareness (X) has an influence on the performance of Airside Officers (Y) at El Tari Kupang Airport by 83.6%.